Review of the Cenozoic Floras and Vegetation of Greece - Velitzelos, Dimitrios; Bouchal, Johannes M; Denk, Thomas (Review of Palaeobotany and Palynology)
Oligocene to Pleistocene floras of Greece are reviewed based on published and unpublished material. Oldest plant-bearing sediments of Rupelian-Chattian age are exposed in eastern Thrace (Evros) and were deposited after the closure of the Turgai Seaway. They contain a blend of (i) taxa that migrated to western Eurasia from the East (Alnus, Fagus), (ii) characteristic Oligocene taxa (Nyssa altenburgensis, Ampelopsis hibschii), and (iii) extinct (Eotrigonobalanus, Quasisequoia) and modern genera (Calocedrus, Quercus Group Lobatae) from older epochs. Coastal palm swamps and laurel forests of the hinterland indicate a subtropical, fully humid to winter-dry climate (Cfa, Cwa according to Köppen). The Aquitanian-Burdigalian plant assemblage of Lesbos is intermediary between Evros and the Burdigalian floras of Euboea sharing taxa with Evros (palms), and with Euboea and early Miocene floras of Anatolia (Güvem, Tilia). In the early Miocene (Burdigalian) floras of Euboea, species of Quercus Group Ilex (Q. drymeja, Q. mediterranea) characteristic of fully humid or winter-dry (monsoon) climates (Cf, Cw) became dominant elements in well-drained forests. Floristic links are with late Oligocene to middle Miocene floras of Central Asia (Tilia), Asia Minor (cycads, Quercus Group Ilex, Tilia), and South and Central Europe (cycads, Quercus Group Ilex, palms). Middle Miocene floras are restricted to the Aegean islands (Chios). Biogeographic links are with early to late Miocene floras of Central Europe (Parrotia, Podocarpium) and with middle Miocene floras of Anatolia (Parrotia). Upper Miocene plant-bearing sedimentary formations are most abundant in Greece and exposed on the Ionian Islands, Greece mainland to East Macedonia, Peloponnese, Aegean Islands, and Crete. Overall, the fossil plant assemblages from Greece mainland are indicative of fully humid conditions during this time (Cfa), with Fagus and oaks of Quercus Group Ilex being dominant elements. Seasonality may have been more pronounced on the Peloponnese and the Aegaean Islands and Crete, expressed by the rare occurrence of Fagus in the fossil records of these areas. The palaeobotanical records from Samos unambiguously point to the presence of forest vegetation during early Tortonian to Messinian (Cwa) when the famous vertebrate faunas of Samos were deposited. The Pliocene is characterized by the regional occurrence of modern types of deciduous oaks mainly of Quercus Group Cerris and Quercus subsect. Galliferae. East Asian links persist in Fagus, Quercus, and Cupressaceae, North American ones in Sabal; several other mesophytic taxa from previous periods are recorded as well. The modern sclerophyllous Mediterranean vegetation, thriving in a warm summer dry climate (Csa), cannot be traced prior to the Pleistocene based on the palaeobotanical record.
Keywords: Cenozoic; Eastern Mediterranean; greece; landscape evolution; Mediterranean climate; plant evolution

Influence of cattle grazing on the density of oak seedlings and saplings in a Tabor oak forest in Israel - Dufour-Dror, Jean-Marc (Acta Oecologica, 2007)
The effects of cattle grazing on the density of seedlings and saplings in a Tabor oak forest (Quercus ithaburensis subsp. ithaburensis) are investigated. The Tabor oak forest studied is located in a Nature Reserve in the Mediterranean region of Israel. Cattle graze at a stocking density of 0.71 head/ha for 6 months a year. The cattle grazing in the Nature Reserve is a beneficial management measure because it enhances plant species richness and reduces shrub encroachment. The impact of grazing on the densities of seedlings and young saplings was quantified in 46 large sampling plots (333 m2 each) distributed over two experimental sites; the first being used as a rangeland for decades while the second is a forest patch totally free from grazing. The density and the height of Tabor oak individuals in each sampling plot were recorded. Four height categories were distinguished with a special focus on young seedlings (<0.15 m), established seedlings and young saplings (0.15 m–1 m). The density of seedlings and young sapling in the grazed Tabor oak forest were, respectively, 61% to 67% lower than in the ungrazed treatment. Implications on the continuity of the entire Tabor oak forest ecosystem are discussed. Three management measures that enable to prevent a decrease in young oak densities are proposed – reduction of stocking rate, deferment of the commencement of grazing, and fencing young seedlings.
Keywords: Eastern Mediterranean; Israel; Management measures; Mediterranean deciduous oak forest; quercus ithaburensis subsp ithaburensis

Influence of cattle grazing on the density of oak seedlings and saplings in a Tabor oak forest in Israel - Dufour-Dror, Jean-Marc (Acta Oecologica, 2007)
The effects of cattle grazing on the density of seedlings and saplings in a Tabor oak forest (Quercus ithaburensis subsp. ithaburensis) are investigated. The Tabor oak forest studied is located in a Nature Reserve in the Mediterranean region of Israel. Cattle graze at a stocking density of 0.71 head/ha for 6 months a year. The cattle grazing in the Nature Reserve is a beneficial management measure because it enhances plant species richness and reduces shrub encroachment. The impact of grazing on the densities of seedlings and young saplings was quantified in 46 large sampling plots (333 m2 each) distributed over two experimental sites; the first being used as a rangeland for decades while the second is a forest patch totally free from grazing. The density and the height of Tabor oak individuals in each sampling plot were recorded. Four height categories were distinguished with a special focus on young seedlings (<0.15 m), established seedlings and young saplings (0.15 m–1 m). The density of seedlings and young sapling in the grazed Tabor oak forest were, respectively, 61% to 67% lower than in the ungrazed treatment. Implications on the continuity of the entire Tabor oak forest ecosystem are discussed. Three management measures that enable to prevent a decrease in young oak densities are proposed – reduction of stocking rate, deferment of the commencement of grazing, and fencing young seedlings.
Keywords: Eastern Mediterranean; Israel; Management measures; Mediterranean deciduous oak forest; quercus ithaburensis subsp ithaburensis

Eastern Mediterranean Quaternary paleoclimates from pollen and isotope records of marine cores in the Nile Cone Area - Cheddadi, Rachid; Rossignol-Strick, M (Paleoceanography, 1995)
Pollen spectra from three eastern Mediterranean cores have been used to document the paleoclimates of the Levantine Basin borderlands over the last 250 kyr to establish the relationship between this regional climate data set and the global climate as recorded by foraminiferal δ18O and to compare it with proximal land pollen records. Core MD 84 642 with eight sapropels covers the last two climatic cycles up to the early Holocene, MD 84 627 with four sapropels goes back to 125 kyr, and MD 84 629 with one sapropel covers the last 70 kyr. The sedimentation rate decreases from core 629, located at the shallowest depth beneath the Nile River plume, to cores 627 and 642. During the interglacials defined by a low 18O/16O ratio, the abundance of tree pollen is maximum and points to an optimum Mediterranean climate with greatest humidity, including some summer rainfall. During glacial maxima, with highest 18O/16O ratio, the pollen abundance is high for steppe and semidesert plants and low for trees, indicating a definitely more arid, more continental, and probably colder climate. The variations of pollen abundance occur in phase with those of the foraminifer δ18O record. This signifies that the regional climate of the Levantine Basin borderlands had the same temporal pattern as the global ice volume documented by the ice volume curve.
Keywords: climate; Eastern Mediterranean; Evergreen and deciduous forests; isotopic stratigraphy (voyant); pollen spectra